The Effect of Industrial Work Practice Experience and Entrepreneurship Education on Interest in Entrepreneurship Using Social Media as a Moderating Variable - Kustiadi Basuki; Sherlina Gratia (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this study was to determine the effect of industrial work practice experience and entrepreneurship education on entrepreneurial interest and the use of social media as a moderating variable. This research model is a quantitative study with a sample of 200 people obtained through a questionnaire in google form distributed on social media. The results obtained by the research show that entrepreneurship education and the use of social media have a positive and significant effect on interest in entrepreneurship, but the use of social media cannot be a moderating variable on the effect of industrial work practice experience on interest in entrepreneurship.